Cefepime-Induced Encephalopathy and Nonconvulsive Status Epilepticus: Dispelling an Artificial Dichotomy. (April 2019) - Tchapyjnikov, Dmitry; Luedke, Matthew W.
Cefepime is a fourth-generation cephalosporin antibiotic known to have neurotoxic side effects. Recent reports have described patients on cefepime presenting with altered mentation and concurrent triphasic wave discharges on electroencephalogram (EEG). Some have described this clinical presentation as cefepime-induced encephalopathy, while others have termed it as cefepime-induced nonconvulsive status epilepticus (NCSE). We report on 4 patients who developed cefepime-associated altered mentation with triphasic discharges on EEG. A benzodiazepine trial was attempted in 3 of the patients, all of whom had improvement in the frequency of the triphasic discharges, but only 2 of whom demonstrated a concurrent partial and transient improvement in mental status. All 4 patients had normalization of mental status upon discontinuation of cefepime. We provide a literature review of prior cases and propose that these reports, including those labeled as NCSE, are best described as a cefepime-induced encephalopathy with triphasic discharges as opposed to an ictal phenomenon. We contend that aggressive treatment with anti-seizure medications is not warranted and that cefepime discontinuation is the definitive treatment. This case series and review of the literature clarifies a long-standing terminological ambiguity in a unique clinical picture that can be encountered by the neurohospitalist or other providers.